An international branch campus in China: a study of intentions to study abroad - Yang, Hongqing (2021)
International Branch Campuses (IBCs) are growing rapidly worldwide, particularly in emerging countries, such as China. A literature review finds that there are contradictions among home and host countries in the economic rationales for establishing IBCs. In theory, both home and host countries would like to benefit from IBCs; however, in practice, most Chinese IBC undergraduates go on to study abroad after graduation and the contribution they make to China’s development becomes a concern. This research aims to understand the contradiction by examining intentions to study abroad at an IBC in China.